2015
DOI: 10.1002/jbm.a.35579
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of biomaterial‐induced multinucleated giant cells: Possible importance for the regeneration process?

Abstract: Biomaterial-associated multinucleated giant cells (BMGCs) have been found within the implantation beds of many different biomaterials. However, their exact differentiation and their involvement in the inflammatory and healing events of the foreign body response still remain mostly unclear. Silk fibroin (SF) scaffolds, which induces a tissue reaction involving both macrophages and BMGCs, was implanted in the subcutaneous connective tissue of four CD-1 mice for 15 days using an established subcutaneous implantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(115 citation statements)
references
References 25 publications
6
107
1
1
Order By: Relevance
“…MNGCs, similar to their precursors (macrophages), were suggested to be able to polarize to M1 or M2 subtypes and may therefore demonstrate contribution to the biomaterial‐based regeneration process . In this context, an in vivo study evaluated the inflammatory pattern of the MNGCs induced by the subcutaneous implantation of silk fibrion in CD‐1 mice . The results showed that biomaterial‐induced MNGCs exhibited a similar heterogeneity as macrophages; thus, MNGCs expressed M1 signaling molecules (Cox‐2, CCR‐7, and NF‐Kb) and M2 signaling molecules (CD‐206 and HO‐1) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MNGCs, similar to their precursors (macrophages), were suggested to be able to polarize to M1 or M2 subtypes and may therefore demonstrate contribution to the biomaterial‐based regeneration process . In this context, an in vivo study evaluated the inflammatory pattern of the MNGCs induced by the subcutaneous implantation of silk fibrion in CD‐1 mice . The results showed that biomaterial‐induced MNGCs exhibited a similar heterogeneity as macrophages; thus, MNGCs expressed M1 signaling molecules (Cox‐2, CCR‐7, and NF‐Kb) and M2 signaling molecules (CD‐206 and HO‐1) .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, an in vivo study evaluated the inflammatory pattern of the MNGCs induced by the subcutaneous implantation of silk fibrion in CD‐1 mice . The results showed that biomaterial‐induced MNGCs exhibited a similar heterogeneity as macrophages; thus, MNGCs expressed M1 signaling molecules (Cox‐2, CCR‐7, and NF‐Kb) and M2 signaling molecules (CD‐206 and HO‐1) . However, to the best of our knowledge no studies have yet investigated the polarization pattern of MNGCs induced by different biomaterials compared to the physiological inflammatory pattern in non‐augmented bone in human tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described [5,16], the PRF clots were collected after 10 days and fixed in Roti ® -Histofix 4%, acid free (pH 7), and 4% phosphate-buffered formaldehyde solution (Carl-Roth) for 24 h. The PRF-based matrices were dehydrated in a series of alcohol and xylene through a Tissue Processor (TP1020, Leica Biosystems Nussloch GmbH, Germany) and embedded in paraffin blocks. Afterwards, 3 µm thick sections from each sample were cut by a rotatory microtome (Leica RM2255, Wetzlar, Germany).…”
Section: Immunohistological Analysismentioning
confidence: 99%
“…Segundo (Barbeck et al, 2016), as CGMs devem ser consideradas como um "sincício funcional" de macrófagos, que reagem similarmente a seus precursores mononucleares frente a um determinado material. (Anderson e Jones, 2007;Jones et al, 2007;Anderson et al, 2008;Ghanaati et al, 2010).…”
Section: Volume Total De Tecido Conjuntivounclassified